1995
DOI: 10.1346/ccmn.1995.0430210
|View full text |Cite
|
Sign up to set email alerts
|

The Rheological and Colloidal Properties of Bentonite Dispersions in the Presence of Organic Compounds V. Bentonite and Sodium Montmorillonite and Surfactants

Abstract: Abstract--The influence of surfactants on the flow behavior of sodium montmorillonite dispersions (2% w/w) was studied for a cationic (cetylpyridinium chloride, CPC1) and an anionic surfactant (sodium dodecylsulfate, SDS). When the dispersion pHs were >3.5 and <7, CPC1 concentrations >10 -4 M increased the shear stress but the Bingham yield value remained virtually unchanged (to ~-100 mPa). At pH ~ 7, the shear stress and yield point decreased with increasing CPC1 concentration (70 from 430 to 100 mPa). The fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 32 publications
1
47
0
Order By: Relevance
“…The rheological properties of suspensions of industrial clays such as bentonites and kaolins have been studied extensively in the past and it is well known that it is affected by particle size and shape, clay concentration, type of exchangeable cation, pH, electrolyte concentration and layer charge (Heath and Tadros, 1983;Brandenburg and Lagaly, 1988;Lagaly, 1989;Permien and Lagaly, 1995;Keren, 1988;. In contrast the rheological properties of palygorskite suspensions have been studied to a lesser degree.…”
Section: Introductionmentioning
confidence: 99%
“…The rheological properties of suspensions of industrial clays such as bentonites and kaolins have been studied extensively in the past and it is well known that it is affected by particle size and shape, clay concentration, type of exchangeable cation, pH, electrolyte concentration and layer charge (Heath and Tadros, 1983;Brandenburg and Lagaly, 1988;Lagaly, 1989;Permien and Lagaly, 1995;Keren, 1988;. In contrast the rheological properties of palygorskite suspensions have been studied to a lesser degree.…”
Section: Introductionmentioning
confidence: 99%
“…Among possible alternative solutions is the strict environmental control of the temperature and relative humidity in the storage room. A treatment that would reduce the swelling capacity of the clay by exchanging the counterion (Na) for another with fewer hydration layers around the cation (Ca or Mg), in theory, should stabilize the clay structure by inducing aggregation of the clays and reduced swelling (Permien and Lagaly 1995). However, a practical method for accomplishing this without water-induced destruction of the stone has not been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a practical method for accomplishing this without water-induced destruction of the stone has not been proposed. Other possible conservation methods involve the application of surface active agents (surfactants) that have been reported to influence both the rheological and swelling properties of clays (van Olphen 1977;Permien and Lagaly 1995). By being fixed on the clay surface, these surface active agents influence the counterion distribution in the Stern and the diffuse ionic layers, resulting in a reduction of the swelling capacity of the clays.…”
Section: Discussionmentioning
confidence: 99%
“…Rand et al (1980) found no evidence for E-F coagulation in the pH range 4-11, in the presence of electrolyte at low concentration. The secondary electroviscous effect was the mechanism proposed by Rand et al (1980) and adopted by Permien and Lagaly (1994) for the minimum in yield stress and plastic viscosity; they suggested that the diffuse double layers around the particles affect their motion. At low electrolyte concentration in clay suspension, the extended diffuse double layer allows more freedom of movement under stress, whereas at higher electrolyte concentration the attractive forces between clay platelets dominate, and the yield stress and plastic viscosity increase again.…”
Section: Introductionmentioning
confidence: 96%